Maternal ventilation and sedation for H1N1 influenza resulting in fetal bladder rupture and urinary ascites. Issue 1 (29th July 2012) - Chaudhari, Tejasvi; Robertson, Meiri; Ellwood, David; Simpson, Erroll; Kecskes, Zsuzsoka; Kent, Alison L
Abstract Urinary ascites in a newborn infant is unusual and most commonly results from bladder perforation following umbilical arterial catheterisation or obstructive uropathy. The following report describes a case of fetal bladder rupture with urinary ascites in a mother ventilated and sedated with narcotics and benzodiazepines for H1N1 influenza. This was associated with a unique biochemical profile of hyponatraemia and elevated serum urea and creatinine characteristic of urinary autodialysis in the neonate.